Comparison of the effectiveness of proprioceptive and isometric exercises in Patients of knee osteoarthtitis: A randomized control trail - Sana Naqi; Aadil Ameer Ali; Mahnoor Bugti; Naseebullah Sheikh; Muhammad Khan Bugti; Shahmeer Chandio; Amjad Hussain; Muhammad Ishque MR; Taufiq Ahmad (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2021)
Objective: Assessment of the effectiveness of proprioceptive and isometric exercises in patients of knee osteoarthritis (OA). Methods: The experimental study was conducted among the 40 patients who had confirmed diagnosis of knee OA. The 40 patients were randomized into separate two groups A & B. The group A received proprioceptive exercise, whereas group B were given the isometric exercises. The data was collected before and after the treatment by using the visual analogue scale for assessing the pain intensity, whereas the analogue goniometer was used for assessing the range of motion of knee joint. After collection, the data was analyzed by using statistical packages for social sciences (Spss) version 22. Results: Patients of group A were heaving the mean age of (45.24 ± 11.52) and the patients of group B were having the mean age of (50.25 ± 12.12). Among the patients of group A, after the treatment the Knee range of motion was (113, ± 7.042), whereas among the patients of group B that was (107, ± 6.601). During the check of Vas scale, group A patients reported (4.01, ± 1.197) and group B reported (3.69, ± 1.054). Proprioceptive and isomeric exercises were statistically significant (p<0.05) to flexion range of motion and pain intensity, separately.  Discussion: In current study the both exercises (proprioceptive & isometric were significant in the management of Knee OA patients. Furthermore the proprioceptive exercises were found significant in enhancing the range of motion of knee joint), while the isometrics gave good results in pain management.